Pengaruh Penggunaan Berbagai Basa dan Pati dalam Pembuatan Cincau Hitam Instan terhadap Sifat-Sifat Fisik Gel yang Dihasilkan - Anisa A. Kartikaningrum; Haryadi Haryadi; Djagal W. Marseno (agriTECH, 2001)
Instant black cincau was prepared by the processing steps involving extraction of "janggelan" using alkaline solution, drying of the extract, and blending of the dried extract with starch. Various alkalines of diffener valence, i.e. NaOH, Mg(OH)2 and Ca(OH)2 at pH 10 were used to extract "janggelan" at the proportion of 50 g/100 ml of alkaline for 60 minutes at boiling condition. Arenga, sago, maize, mung bean. tapioca and soft rice starches were used to blend the dried extracts. The proportions of dried extracts used were at 1.5, 2.0 and 2.5 g per 7.5 g starch. Gels were prepared by boiling the blended stuffs in 250 ml water and allowed to cool to room temperature. The gels were characterized for breaking strength, elasticity and syneresis. The results indicated that the use of divalent alkaline gave higher strength, equal elasticity, and higher syneresis of the gels compared to that of monovalent alkaline. All the starches containing 20.6-47.1 % amylose, excluding soft rice, gave sompact gels. The use of starch containing 11.9 % amylose did not form gel. The increase in proportion of dried extract to starch caused higher breaking strength, but lower elasticity and syneresis of the gels.